ANALISIS PERMAINAN BAHASA DAN BAHASA PRIBADI PADA HANS CRISTIAN ANDERSEN (THE LITTLE MATCH GIRL) - Saputri, Tiyas (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2020)
This research focuses on a syntactical analysis of The Little Match Girl, a short story by Hans Christian Andersen, based on Wittgenstein’s language games and private languages theories. The story is about a dying child’s dreams and hope. In this short story, there are some arrangements of sentence structure which do not obey the rules of grammar. The objective of the study is to analyze this short story syntactically, which uses some formulated grammar rules to map a sentence to a formal representation of its syntactic structure, which is also a part of the theory. The research method was descriptive qualitative. To collect the data, the researcher used documentation and observation methods. In the analysis, the researchers analyzed by using grammar rules then presented in form of tables. The finding showed that some sentences do not obey the grammar rules (private language) in 1a, 2a, 3a, 4a, 5a, 6a, and 7a but then they are checked in the correct grammar and corrected (language game) (see 1b, 2b, 3b, 4b, 5b, 6b, and 7b). However, they are still understandable because it is easy to understand the content of the story of The Little Match Girl as he has his own specific private languages to get aesthetics of writing. To conclude, Hans Cristian Andersen has his own specific private languages so that he does not obey the grammar rules in writing his short story because it is part of poetical license.